Implementasi Pendidikan Karakter Dalam Mendukung Gerakan Penguatan Pendidikan Karakter Di SD Muhammadiyah 9 Malang - Rosyida, Ruli Alfi Mei; Juanda, Ahmad; Syahri, Mohammad (Jurnal Kebijakan dan Pengembangan Pendidikan, 2019)
Abstract: The negative impact of globalization is the increasingly worsening character of the younger generation. In overcoming the problem of demoralizing the younger generation, the Government of Indonesia issued a policy of strengthening character education. This study aims to describe (1) the implementation of character education to support strengthening character education(PPK) movement at elementary school Muhammadiyah 9 Malang. (2) supporting and inhibiting factors in the process of character education implementation in the context of supporting the PPK movement at elementary school Muhammadiyah 9 Malang. This research is a qualitative descriptive study, located at elementary school Muhammadiyah 9 Malang, with data collection techniques in the form of interviews, observations, and documentation. The results showed that (1) the implementation of PPK policies in schools was not much different from the character education programs that had previously been implemented. Strengthening the character education that runs is to add a variety of character planting habituation programs, increase the hours of character habituation activities, increase student learning activities and intensify a variety of programs that are already running at school. Schools implement the PPK movement according to the Ministry of Education and Culture's reference with three basic approaches. (2) Supporting factors are none other than full support provided by all schools and parents of students while inhibiting factors faced by schools are none other than students themselves and there are parents of students.Keywords: Policy, Strengthening Character Education, Elementary SchoolsÂ Abstrak: Dampak yang dihasilkan globalisasi secara negatif yaitu semakin memburuknya karakter generasi muda. Dalam mengatasi persoalan demoralisasi generasi muda Pemerintah Indonesia mengeluarkan kebijakan penguatan pendidikan karakter. Penelitian ini bertujuan untuk mendeskripsikan (1) implementasi pendidikan karakter dalam rangka mendukung gerakan PPK di SD Muhammadiyah 9 Malang. (2) faktor pendukung dan penghambat proses impelementasi pendidikan karakter dalam rangka mendukung gerakan PPK di SD Muhammadiyah 9 Malang. Penelitian ini merupakan penelitian deskriptif kualitatif, bertempat di SD Muhammadiyah 9 Malang, dengan teknik pengumpulan data berupa wawancara, observasi, dan dokumentasi. Hasil penelitian menunjukkan bahwa (1) implementasi kebijakan PPK di sekolah tidak jauh berbeda dengan program pendidikan karakter yang sebelumnya sudah dilaksanakan. Penguatan pendidikan karakter yang berjalan yaitu dengan menambah berbagai program pembiasaan penanaman karakter, menambah jam kegiatan pembiasaan karakter, menambah kegiatan pembelajaran siswa dan mengintensifkan berbagai program yang sudah berjalan di sekolah. Sekolah mengimplementasikan gerakan PPK sesuai acuan kemendikbud dengan tiga basis pendekatan. (2) Faktor pendukung tidak lain berupa dukungan penuh yang diberikan oleh seluruh pihak sekolah dan orang tua siswa, sedangkan faktor penghambat yang dihadapi sekolah tidak lain berasal dari para peserta didik sendiri dan ada dari orang tua siswa.Kata kunci: Kebijakan, Penguatan Pendidikan Karakter, Sekolah Dasar